Efficacy of Closed Reduction Perutaneous Pinning and Laeral Pinning in the Treatment of Supracndylar Fracture of Humerus in Children - Zaryab Muhammad, Muhammad Khubaib, Syed Sarmad Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Closed reduction percutaneous cross pinning vs. lateral pinning in the treatment of children's supracondylar humeral fractures is the goal of this research. Study Design: Prospective study Place and Duration: THQ hospital Jaranwala/ Punjab medical college Faisalabad. Feb 2021-Aug 2021 Methods: This research included a total of 90 patients of both sexes. After obtaining informed permission, demographic information such as gender, age, and BMI was gathered. Patients ranging in age from 2 to 15 years old were taken into consideration for treatment. Two groups of children with fractures of the supracondylar humerus were recruited and randomized. In the first group, 45 patients got percutaneous cross pinning, whereas in the second group, 45 patients had lateral pinning performed on them. Both groups' radiological and functional outcomes were evaluated using Flynn's criteria, and a high incidence of problems was noted. SPSS 24.0 was used to analyze all of the data. Results: Total 60 (66.7%) patients were males and 30 (33.3%) cases were females. There was no any significant difference of age among both groups. Most common cause of fracture was sports and road traffic accident. In group I mean surgical time was 28.12±4.04 minutes and mean time in group II was 32.21±4.31 minutes. We found mean radiation time in group I was greater 4.11±5.41 sec than in group II radiation time was 3.21±4.5 sec. According to Flynn's criteria, excellent results were found in 29 (64.4 %) cases, good results were found in 10 (22.2 %), and fair results were found in 6 (13.3 %) cases in group I, while excellent results were found in 24 (53.3 %) cases, good results were found in 13 (28.9 %), and fair results were found in 8 (17.8%) cases in group II. Conclusion: After conducting this study, we came to the conclusion that both methods for the treatment of closed reduction supracondyla fractures of the humerus are safe and effective for children; however, percutaneous pining was found to be less operative and required more radiation time than two lateral pinnings.